The nature of nothing: exploring the quantum vacuum in microgravity. (1st January 2023) - Thompson, Rob
Abstract: In this paper we discuss a number of investigations of the quantum vacuum that could potentially take advantage of a microgravity environment. Ultra-cold atoms are exquisite sensors of the electro-magnetic vacuum, and microgravity aids our ability to precisely position and control them in the vicinity of surfaces and cavity modes. Measurements of Casimir–Polder force, Anderson localization and the possibilities for confining atoms with vacuum forces are amongst the intriguing possibilities discussed.